Feeling the Conflict: The Crucial Role of Conflict Experience in Adaptation. (March 2014) - Desender, Kobe; Van Opstal, Filip; Van den Bussche, Eva
In the study reported here, we examined the role of conflict experience in cognitive adaptation to conflict. Although the experience of conflict is generally neglected in theoretical models of cognitive control, we demonstrated that it plays a critical role in cognitive adaptation. Using a masked-priming paradigm, we showed that conflict adaptation was present only after trials on which participants experienced response conflict. Furthermore, when subjective experience did not coincide with actual conflict, adaptation effects in the error rates were observed after the experience of conflict, not after response conflict. We conclude that the experience of conflict, and not response conflict per se, is the crucial factor underlying cognitive adaptation effects. The current findings provide a new perspective on the question of why the human cognitive system exerts cognitive control, and they suggest that a crucial role of subjective experience is to allow for top-down control of behavior.